Functional MAIT Cells Are Associated With Reduced Simian–Human Immunodeficiency Virus Infection - Murugesan, Amudhan; Ibegbu, Chris; Styles, Tiffany M.; Jones, Andrew T.; Shanmugasundaram, Uma; Reddy, Pradeep B. J.; Rahman, Sadia J.; Saha, Piu; Vijay-Kumar, Matam; Shankar, Esaki Muthu; Amara, Rama Rao; Velu, Vijayakumar (Frontiers in Immunology, 2020)
Mucosa-associated invariant T-cells (MAIT) are recently characterized novel subset of innate-like T-cells that recognize microbial metabolites presented by MHC-1b-related protein MR1. The significance of MAIT cells in anti-bacterial defense is well understood but not clearly in viral infections such as SIV/HIV infection. Here, we studied the phenotype, distribution, and function of MAIT cells and their association with plasma viral levels during chronic SHIV infection in rhesus macaques (RM). Two groups of healthy and chronic SHIV-infected macaques were characterized for MAIT cells in blood and mucosal tissues. Similar to human, we found a significant fraction of macaque T cells co-express MAIT cell markers CD161 and TCRVα-7.2 that correlated directly with macaque MR1 tetramer. These cells displayed memory phenotype and expressed high levels of IL-18R, CCR6, CD28, and CD95. During chronic infection, the frequency of MAIT cells are enriched in the blood but unaltered in the rectum, both blood and rectal MAIT cells displayed higher proliferative and cytotoxic phenotype post SHIV infection. The frequency of MAIT cells in blood and rectum correlated inversely with plasma viral RNA levels and correlated directly with total CD4 T cells. MAIT cells respond to microbial products during chronic SHIV infection and correlated positively with serum flagellin levels. Tissue distribution analysis of MAIT cells during chronic infection showed significant enrichment in the non-lymphoid tissues (lung, rectum, and liver) compared to lymphoid tissues (spleen, LN) with higher levels of tissue resident markers CD69 and CD103. Exogenous in vitro cytokine treatments during chronic SHIV infection revealed that IL-7 is important for the proliferation of MAIT cells, but IL-12 and IL-18 are important for their cytolytic function. Overall our results demonstrated that MAIT cells are enriched in blood but unaltered in rectum during chronic SHIV infection, which displayed proliferative and functional phenotype that inversely correlated with SHIV plasma viral RNA levels. Treatment such as combined cytokine treatments could be beneficial for enhancing functional MAIT cells during chronic HIV infection in vivo.